Corrosion behaviour of an indigenous Ag-Sn-Cu cast dental alloy in artificial saliva - Patro T.K.; Singh B.P.; Singh V. (My University, 2025)
The corrosion behaviour of an indigenous cast alloy of Ag-Sn-Cu, developed for crown and bridge prostheses, was studied in artificial saliva, with and without the addition of 0.1 M lactic acid, using a potentiostatic technique, and compared with that of the standard cast alloy of Ag-Pd (Ney 76). The values of different parameters such as corrosion potential and corrosion current density were determined for the indigenous alloy of Ag-Sn-Cu and the Ag-Pd alloy. The rate of corrosion of the indigenous alloy was found to be relatively higher than that of the Ag-Pd alloy up to an applied potential of + 400 mV. However, while the indigenous alloy showed a distinct tendency for passivation below + 200 mV at the current level of 0.5 mA/cm2 in the artificial saliva (pH 5.7) at 37°C, no such tendency for passivation was shown by the Ag-Pd alloy even up to + 400 mV. The tendency for passivation by the indigenous Ag-Sn-Cu alloy, however, was not shown in the artificial saliva in the presence of 0.1 M lactic acid (pH. 2.7) at 37°C. Minor variation was observed in the corrosion behaviour of the indigenous Ag-Sn-Cu alloys of different grades prepared by alloying elements of varying purity. © 1998 Blackwell Science Ltd.